Varsity Boat Club on Union Bay, ca. 1916
University of Washington crew coach Hiram Conibear managed to procure the Coast Guard station and lighthouse from the 1909 Alaska-Yukon-Pacific Exposition for use as the new crew boathouse. Located at what had been the foot of the Exposition's Pay Streak, the new Varsity Boat Club was established in 1910 under Conibear as a social organization for all of the upperclassmen who rowed on the team. This "temporary" building on Portage Bay would house the team through 1918. Newspaper caption glued onto verso: Home of the Varsity Boat Club, the Husky sweepsters, during the reign of Hiram Boardman Connibear [sic], the old shell house at the foot of Pay St. in Union Bay holds many rowing memories for an older generation of the U. of W. Drawn on front of photo: White cropping marks and pencil notations for printing in Seattle Post-Intelligencer newspaper Caption information source: http://www.huskycrew.com/. 1 photographic print: b&w; 5 x 7 in.